The control of pressure in constant rate cake filtration - Steve Tarleton (1998)
The widespread reliance on heuristics for the design and specification of particle/fluid separation devices has prompted a new approach to pressure filtration incorporating the principles of mechatronics. A unique experimental apparatus is described and used to obtained filtration data for aqueous mineral suspensions forming either incompressible or moderately compressible filter cakes. Data for constant flow filtrations are presented where the air pressure within the filter is controlled through flow & pressure transducers and an electronically adjusted pressure regulator. Their combination allowed filtrations performed under different pressure/flow regimes to be compared. It is shown how scale-up data obtained from constant pressure filtrations can produce erroneous predictions of constant rate filtration behaviour, particularly as cake compressibility increases.